Specification of the embryonic limb primordium by graded activity of Decapentaplegic. - Goto, S.; Hayashi, S. (Development, 1997)
Two thoracic limbs of Drosophila, the leg and the wing, originate from a common cluster of cells that include the source of two secreted signaling molecules, Decapentaplegic and Wingless. We show that Wingless, but not Decapentaplegic, is responsible for initial specification of the limb primordia with a distal identity. Limb formation is restricted to the lateral position of the embryo by negative control of the early function of Decapentaplegic and the EGF receptor homolog that determine the global dorsoventral pattern. Late function of Decapentaplegic locally determines two additional cell identities in a dosage dependent manner. Loss of Decapentaplegic activity results in a deletion of the proximal structures of the limb, which is in contrast to the consequence of decapentaplegic mutations in the imaginal disc, which cause a deletion of distal structures. The results indicate that the limb pattern elements are added in a distal to proximal direction in the embryo, which is opposite to what is happening in the growing imaginal disc. We propose that Wingless and Decapentaplegic act sequentially to initiate the proximodistal axis.